Fabrication of statical friction coefficient determination system in inclined plane using microcontroler - Maisa Fitri (Department of Physics – Universitas Negeri Padang UNP, 2014)
Research has been done to design a system of determination of the static friction coefficient of the object on inclined plane digitally. The purpose of this research is to explain the performance specifications, accuracy and precision of the system. There are three results of this research. First, The system is designed with the surface of the slip object size 8.7 x15 cm and glide plane 9 x 100 cm. Second, average of precision relative sensor accelerometer is 95,58%. Third, average accuration is 0,977